A carne na dieta alimentar em Vila Boa de Goiás: necessidades e preferências nos séculos XVIII e XIX - Alencastro, Elaine de (2014)
This work has as main goal to enhance the knowledge about the food habits of Goiás City inhabitants, former Vila Boa, between the centuries XVIII and XIX. To this purpose the specific samples of faunal remains of the main streets of this current historic center will be analyzed. The work will have an interdisciplinary perspective - Zooarchaeology, Anthropology and History – this way identifying, in this study, the food trend of acquisition, preparation, consumption and disposal. It’s important to highlight that, thinking about this path analysis, the choices are elected within symbolic codes and standards related to construction of gustatory memory. So, we can associate the faunal remains with the different societies that installs in Vila Boa. That intervenes that vilaboense supply has rules as pathways, patterns of similarities such as the ones which were in vogue throughout the colony